2019
DOI: 10.1016/j.neubiorev.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny vs. phylogeny in primate/canid comparisons: A meta-analysis of the object choice task

Abstract: There may be additional changes during production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Thus, when presenting similar tasks across representatives of different species, it is important to consider how response requirements or expectations interact with life history stage and pre-experimental life experience, to ensure that organisms are given the best opportunity to display their cognitive competencies; for example, it is well-demonstrated that enculturated apes significantly outperform institutionalised apes in similar experimental contexts (Lyn et al, 2010;Russell et al, 2011; and see, in a different context, arguments by Horowitz, 2003, andThomas, Murphy, Pitt, Rivers, &Leavens, 2008, to the effect that younger humans are not representative of adult humans in some cognitive assays). Thus, because previous cross-species comparisons have generally not controlled for life history stage or task-relevant pre-experimental experience (Clark et al, 2019;Krause et al, 2018;Leavens et al, 2019), and because the present study shows a developmental shift in human children toward a reduced reliance on the use of communication in the presence of a barrier, therefore, we recommend a systematic revision to the OCT that permits both communicative HUMAN REFERENTIAL PROBLEM SPACE 26 and praxic responses. This adjustment will foster best performance to be captured and reduce the existing bias towards false negatives in some testing circumstances.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, when presenting similar tasks across representatives of different species, it is important to consider how response requirements or expectations interact with life history stage and pre-experimental life experience, to ensure that organisms are given the best opportunity to display their cognitive competencies; for example, it is well-demonstrated that enculturated apes significantly outperform institutionalised apes in similar experimental contexts (Lyn et al, 2010;Russell et al, 2011; and see, in a different context, arguments by Horowitz, 2003, andThomas, Murphy, Pitt, Rivers, &Leavens, 2008, to the effect that younger humans are not representative of adult humans in some cognitive assays). Thus, because previous cross-species comparisons have generally not controlled for life history stage or task-relevant pre-experimental experience (Clark et al, 2019;Krause et al, 2018;Leavens et al, 2019), and because the present study shows a developmental shift in human children toward a reduced reliance on the use of communication in the presence of a barrier, therefore, we recommend a systematic revision to the OCT that permits both communicative HUMAN REFERENTIAL PROBLEM SPACE 26 and praxic responses. This adjustment will foster best performance to be captured and reduce the existing bias towards false negatives in some testing circumstances.…”
Section: Discussionmentioning
confidence: 89%
“…Working with individuals from other taxonomic groups, domestic dogs or human infants, for example, does not necessitate the use of such safety precautions, and, as such, there is an absence of this barrier in the testing environment with these species; this constitutes a confound between experimental protocol and species classification in a significant number of contemporary studies. In a review of 71 published nonhuman primate and dog OCT studies, Clark et al (2019) found that 99% of nonhuman primates were tested with a barrier present in the testing environment, compared with less than 1% of dogs. They therefore argued that this HUMAN REFERENTIAL PROBLEM SPACE 6 inconsistency in the test set-ups used across different species represents an experimental confound that may affect individuals' performances.…”
mentioning
confidence: 99%
“…Such a resampling approach offers a more formal framework for designing and evaluating "species-fair" comparisons (Boesch, 2007;Brosnan et al, 2013;Eaton et al, 2018;Tomasello & Call, 2008): under this approach, an ideal comparison should sample from different populations of experimental units, but the same relative populations of treatments, measurements and settings (Eaton et al, 2018;MacLean et al, 2012;Tomasello & Call, 2008). (Clark et al, 2019;Leavens et al, 2019;Tomasello & Call, 2008). This need was recognized by animal learning theorists, who attempted to generate pure between-species comparisons by exerting a large amount of control over treatment, measurement and setting variation.…”
Section: Species-fair Comparisonsmentioning
confidence: 99%
“…But in some cases, it is possible to pinpoint likely confounders that are near perfectly correlated with species, and this can be used to reduce confidence in whole bodies of data. For example, Clark et al (2019) highlighted how procedural differences in an object choice task confound speciesdifference inferences between dogs and non-human primates, i.e., the comparisons lack validity because the measurements and settings may be from different relative populations between dogs and primates.…”
Section: Case 2: Programme-wide Confoundsmentioning
confidence: 99%
See 1 more Smart Citation